2016
DOI: 10.1175/bams-d-15-00031.1
|View full text |Cite
|
Sign up to set email alerts
|

XBT Science: Assessment of Instrumental Biases and Errors

Abstract: Expendable bathythermograph (XBT) data were the major component of the ocean temperature profile observations from the late 1960s through the early 2000s, and XBTs still continue to provide critical data to monitor surface and subsurface currents, meridional heat transport, and ocean heat content. Systematic errors have been identified in the XBT data, some of which originate from computing the depth in the profile using a theoretically and experimentally derived fall-rate equation (FRE). After in-depth studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 49 publications
2
73
0
Order By: Relevance
“…It shows a 0-700 m OHC decrease of ∼ −2.67 [−3.28, −2.06] × 10 22 J after El Chichón and ∼ −2.72 [−3.97, −1.47] × 10 22 J after Pinatubo, indicating the strong ocean cooling. The negative radiative forcing to the ocean (and climate system) due to the volcano eruption is probably the major reason for this decrease (Church et al, 2005Balmaseda et al 2013), but our observational analyses can not exclude the possibility that the unforced ocean variability (such as ENSO, Trenberth and Fasullo, 2012) and the insufficiency of data coverage (which could induce spurious interannual OHC change) are fully or partly responsible for the values calculated above, which requires more careful model-based studies in the future. Moreover, it is also suggested that volcanic eruptions can trigger an El Niño-like response in the ocean, which is another possible explanation (Mann et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It shows a 0-700 m OHC decrease of ∼ −2.67 [−3.28, −2.06] × 10 22 J after El Chichón and ∼ −2.72 [−3.97, −1.47] × 10 22 J after Pinatubo, indicating the strong ocean cooling. The negative radiative forcing to the ocean (and climate system) due to the volcano eruption is probably the major reason for this decrease (Church et al, 2005Balmaseda et al 2013), but our observational analyses can not exclude the possibility that the unforced ocean variability (such as ENSO, Trenberth and Fasullo, 2012) and the insufficiency of data coverage (which could induce spurious interannual OHC change) are fully or partly responsible for the values calculated above, which requires more careful model-based studies in the future. Moreover, it is also suggested that volcanic eruptions can trigger an El Niño-like response in the ocean, which is another possible explanation (Mann et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous correction schemes have been proposed to remove the time-varying XBT biases (Cheng et al, 2015b), but these schemes vary in their formulation and performance. Hence, the XBT community met in 2014 and made a series of recommendations on the factors that should be accounted for when designing and implementing an XBT bias-correction scheme (Cheng et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not apply any correction to XBT depths or temperature and we refer to literature for discussions on uncertainties in XBT measurements (e.g. see Cowley et al, 2013;Cheng et al, 2014Cheng et al, , 2015.We note that the robustness and consistency of XBT data has been a well-know problem for dozens of years. Several studies have been published on this subject (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…FRE has an error of about ±5 m or 2% depth that yields a significant uncertainty in temperature measurements (Goes et al 2015a). Hanawa et al (1995) first suggested a correction for XBT FRE biases, and many subsequent studies have continuously proven the negative impact of XBT biases on ocean climate studies (Kizu et al 2005;Gouretski and Koltermann 2007;Domingues et al 2008;Wijffels et al 2008;Levitus et al 2009;DiNezio and Goni 2011;Cowley et al 2013;Goes et al 2013;Cheng et al 2014Cheng et al , 2015. So far, no agreement has been reached on how the XBT data should be corrected before it is used in climate studies.…”
Section: Introductionmentioning
confidence: 99%